Women of value : feminist essays on the history of women in economics - Dimand,Mary Ann(Editor) Dimand Robert W.(Editor) Forget,Evelyn L.(Editor) (E. Elgar, 1995)
Women economists rarely feature in most textbooks on the history of economic thought before 1960, despite the many articles and theses produced by them in the period. Why is their work so little studied? What did they write about? Who listened to them, supported them or hindered them?